Analisis Strategi Komunikasi Politik untuk Membangun Citra Politik - Farah Dalilah Balqis; Hanifah Fitri; Waldi Afalah Sinaga; Sampurna, Ahmad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the political communication strategies used in building a political image. With dynamic changes in the world of politics and media, political communication strategies have become key in shaping public perceptions of political leaders and parties. Qualitative research methods were used to analyze case studies from various political contexts. Key findings highlight the importance of consistent and measurable messages, the use of social media as a key tool in delivering political messages, as well as the strategic role of narratives in influencing public opinion. In addition, identification of the right target audience and adaptation of messages according to their needs are also key elements of a successful political communication strategy. The implications of these findings can help political decision-makers and communication practitioners to be more effective in building and maintaining the desired political image. The development of a more holistic and sustainable political communication strategy can help improve the quality of political dialog, strengthen public participation, and strengthen the overall foundation of democracy.